(untitled) (Italian Journal of Public Health, 2011)
Background: Alzheimer’s Disease is the most common manifestation of dementia affecting almost 24 million people worldwide. It afflicts mainly the elderly. The aims of this study are to provide hospitalization and mortality trends for Alzheimer’s Disease, to provide first evidence about co morbidity in Alzheimer’s Disease and to describe co-morbidity profiles. Methods: Two sources of Alzheimer’s Disease trends were investigated: the main diagnosis from hospital discharges and the underlying cause of death. Co-morbidity was studied by analysing the multiple diagnoses from hospital discharge files and the multiple causes of death from mortality files. Results: Trends of Alzheimer’s Disease are increasing both for hospitalization and for mortality rates. When all diagnoses and multiple causes are considered the patterns are similar. When Alzheimer’s Disease is reported as the main diagnosis in hospital discharges, the diseases more frequently associated with the disease are other mental disorders, hypertensive diseases, cerebrovascular diseases and other diseases of the circulatory system. The diseases most frequently associated with mortality are ill-defined causes, pneumonia, influenza and other diseases of the respiratory system. Moreover, associations between Alzheimer’s Disease and cerebrovascular diseases, and with diseases of the circulatory system, are found in both databases. Conclusions: Data regarding deaths and hospital discharges show similar patterns for Alzheimer’s Disease both for trends and age profiles. Many similarities among the two data sources are also found when analysing co-morbidities. These results highlight the coherence of different data sources and underline the importance of carrying out asystematic analysis of these databases for purpose of improving epidemiological information.